Are the Pathological Characteristics of Prostate Cancer More Aggressive or More Indolent Depending upon the Patient Age?. (7th February 2017) - Ji, Guangjie; Huang, Cong; Song, Gang; Xiong, Gengyan; Fang, Dong; Wang, He; Hao, Han; Cai, Lin; He, Qun; He, Zhisong; Zhou, Liqun
Abstract : Purpose . To identify pathological characteristics of prostate cancer according to patient age at diagnosis. Methods . A retrospective review of 2, 929 men diagnosed with prostate cancer was performed. Pathological characteristics were compared across age groups: ≤55, 56–75, and >75 years. Results . The study cohort included 133 patients (4.5%), 2, 033 patients (69.5%), and 763 patients (26.0%) in the three age groups, respectively. The median pathological Gleason sums in the three age groups were 8, 7, and 8, respectively. The Gleason sum, primary Gleason score, and second primary Gleason score were significantly different among the three age groups (Z = 12.9 75, p = 0.002 ; Z = 9.264, p = 0.010 ; Z = 6.692, p = 0.035, resp.). The percentages of Gleason pattern 5 tumors for the three age groups were 44.4%, 32.3%, and 36.8%, respectively; they were significantly different (χ 2 = 11.641, p = 0.003 ). The percentages of tumors with Gleason score grade groups 3–5 for the three age groups were 66.9%, 60.5%, and 66.3%, respectively; they were significantly different (χ 2 = 9.401, p = 0.009 ). Conclusions . The present study indicated that men aged ≤55 years or >75 years show higher levels of clinically significant prostate cancer compared to patients between the ages of 55 and 75 years. Younger and more elderly male patients are more likely to have a more aggressive disease.